ANALYSIS SUITABILITY THE FIRE PROTECTION SYSTEM AT FACULTY OF PUBLIC HEALTH BUILDING MUHAMMADIYAH JAKARTA UNIVERSITY IN 2023 - Sarah Dyanti Fitria; Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Each building must have a fire protection system, both active and passive, according to the technical requirements of the building. Based on 2016 fire data from the Head of the DKI Jakarta Provincial Fire and Disaster Management Service, from January 1 - August 21 2022 the number of fire incidents reached 8,004 cases. Meanwhile, in South Tangerang City throughout 2022 there were 62 fire cases. The total material losses from the fire cases experienced reached 5.5 billion. Based on 2016 fire data from the Head of the DKI Jakarta Provincial Fire and Disaster Management Service, from January 1 - August 21 2022 the number of fire incidents reached 8,004 cases. Meanwhile, in South Tangerang City itself throughout 2022 there were 62 fire cases. The total material losses from the fire cases experienced reached 5.5 billion. The purpose of the study is to evaluate the Public Health Faculty Building's fire safety system at Muhammadiyah University in Jakarta. In-depth interviews and observation techniques are used in this qualitative, descriptive study. The Faculty of Public Health Building at Muhammadiyah University in Jakarta serves as the research site. Active protection systems, passive protection systems, and life-saving techniques are the variables under investigation. The general staff and the security staff were the two informants in this study. According to the research's findings, the active protection system complies fully with the specifications; nevertheless, one tool remains untested. The requirements are met by the passive protection system. There are still certain facilities that fall short of the standards, even though the life-saving facilities are fully compliant. All things considered, it satisfies the conditions outlined in Minister of Public Works Regulation No. 26/PRT/M/2008. According to this study, the Faculty of Public Health, Universitas Muhammadiyah Jakarta Building's fire safety system satisfies all legal requirements.